The gordian knot of the environmental contentious administrative: The administrative invalidation - Jara, Daniela; Núñez, Álvaro (Revista de Derecho Ambiental, 2017)
The article describes the claim of article 17 N° 8 of Law N° 20.600, re-viewing the main problems that have faced in its judicial process, then analyze the sentenc-es related to administrative invalidation, pausing in those that have received the claims sought. Furthermore, the decisions of the environmental court is reviewed and the term in which the rule is emitted, analyzing whether these procedures ensure effective judicial access in environmental matters. It also examines the possibility that the environmental pro-tection action may be erected as a more efficient legal remedy considering the problems identified in the claim action of article 17 No. 8 of Law No. 20.600. For this, we review the rulings of 2017 that modify the current jurisprudence of the Supreme Court, which was deferent to the specialized judiciary. Finally, a solution is presented to the problems identi-fied, through the application of the principle pro actione, according to which the environ-mental courts should prefer the substantive and definitive solution of the controversies that come to their knowledge, solving the substance of the request of invalidation, leaving only for exceptional cases the return of knowledge to the administration.